A microsatellite polymorphism in the heme oxygenase-1 gene promoter is associated with increased bilirubin and HDL levels but not with coronary artery disease - Endler, Georg; Exner, Markus; Schillinger, Martin; Marculescu, Rodrig; Sunder-Plassmann, Raute; Raith, Marianne; Jordanova, Nelli; Wojta, Johann; Mannhalter, Christine; Wagner, Oswald F.; Huber, Kurt (Thrombosis and Haemostasis, 2004)
Heme oxygenase 1 (HO-1) is involved in the generation of the endogenous anti-oxidant bilirubin which exerts beneficial effects against arteriosclerosis. A (GT) repeat polymorphism in the HO-1 promoter region modulates HO-1 expression in response to oxidative stress. Recently, this polymorphism has been reported to protect from coronary artery disease in Orientals. We intended to confirm this observation in Caucasians.We studied 649 individuals with myocardial infarction (n=258), stable coronary artery disease (n=180) and controls without coronary artery disease (n=211). Carriers of short alleles (<25 repeats) had higher bilirubin levels (median 0.66 mg/dL, IQR 0.49 to 0.91) compared to non-carriers (median 0.61mg/dL, IQR 0.45 to 0.82; p=0.03) and a more favourable lipid profile (HDL median 47mg/dL, IQR 40 to 50 vs. median 45, IQR 37 to 55, p=0.01; triglycerides median 118mg/dL, IQR 87 to 174 vs. median 132, IQR 97 to 191, p=0.03). However, no significant differences of the genotype distribution were observed between the three groups in this Caucasian study population (p=0.94).Although potentially beneficial effects of the short HO-1 allele on lipid profile and serum bilirubin were observed, in contrast to Orientals, the HO-1 genotype was not associated with coronary artery disease in Caucasians.
Keywords: Heme oxygenase 1; promoter polymorphism; coronary artery disease; bilirubin; Caucasians